2018
DOI: 10.1038/s41588-018-0126-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analyses identify 68 new loci associated with intraocular pressure and improve risk prediction for primary open-angle glaucoma

Abstract: Glaucoma is the leading cause of irreversible blindness globally.1 Despite its gravity, the disease is frequently undiagnosed in the community.2 Raised intraocular pressure (IOP) is the most important risk factor for primary open-angle glaucoma (POAG).3,4 Here we present a meta-analysis of 139,555 European participants that identified 112 genomic loci associated with IOP, 68 of which are novel. These loci suggest a strong role for angiopoietin-receptor tyrosine kinase signaling, lipid metabolism, mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
307
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 234 publications
(316 citation statements)
references
References 58 publications
(79 reference statements)
7
307
1
1
Order By: Relevance
“…Both Tie2 and Angpt1 loss of function variants associate with risk of congenital glaucoma, and singlenucleotide polymorphisms in the Angpt1 promoter region significantly associate with primary openangle glaucoma risk (57)(58)(59). Consistent with immunofluorescence data in mice (60,61), our ssRNAseq data show that expression of Angpt1 in the conventional outflow tract is limited to TM cell clusters, while Tek (Tie2) and its antagonist, Angpt2 are expressed by lymphatic/endothelia cell clusters.…”
Section: Cell Type Specific Expression Of Glaucoma-related Genessupporting
confidence: 83%
“…Both Tie2 and Angpt1 loss of function variants associate with risk of congenital glaucoma, and singlenucleotide polymorphisms in the Angpt1 promoter region significantly associate with primary openangle glaucoma risk (57)(58)(59). Consistent with immunofluorescence data in mice (60,61), our ssRNAseq data show that expression of Angpt1 in the conventional outflow tract is limited to TM cell clusters, while Tek (Tie2) and its antagonist, Angpt2 are expressed by lymphatic/endothelia cell clusters.…”
Section: Cell Type Specific Expression Of Glaucoma-related Genessupporting
confidence: 83%
“…As an example, the POAG phenotype may be defined in many different ways: by the associated traits (endophenotypes) cup‐to‐disc ratio (CDR), intraocular pressure (IOP), visual field (VF) loss, or by some combination of these (reviewed in Weinreb, Aung, & Medeiros, ). Fifteen loci have been identified as genetic risk modifiers of disease (Burdon et al., ; Chen et al., ; Cooke Bailey, Hoffman, et al., ; Gharahkhani et al., ; Hysi et al., ; Li et al., ; Thorleifsson et al., ; Wiggs et al., ), and numerous others identified in POAG endophenotypes have recently shown association with POAG (Gao, Huang, Nannini, Fan, & Kim, ; Khawaja et al., ; MacGregor et al., ). The genetic factors identified in studies of POAG and its component phenotypes (such as IOP, CDR, VF changes) overlap but are not identical.…”
Section: Critical Parameters and Complicating Factorsmentioning
confidence: 99%
“…Reports have shown that incidence rate of glaucoma is higher in siblings compared with unrelated controls, indicating an important role of host genetics in predisposition to glaucoma. Recent genome wide association studies reveled role of ATP‐binding cassette transporter A1, actin filament‐associated protein 1, GDP‐mannose 4,6 dehydratase, phosphomannomutase 2, transforming growth factor beta receptor III, fibronectin type III domain containing 3B, rho guanine nucleotide exchange factor 12, growth arrest‐specific protein 7, forkhead box C1, ataxin‐2, thioredoxin reductase 2 with POAG, and PACG showed to be linked to ependymin related 1, choline acetyltransferase, gli‐similar protein 3, fermitin family member 2, and dolichyl‐phosphate mannosyltransferase subunit 2 . Furthermore, various candidate gene association studies presented association of single nucleotide polymorphisms with predisposition to development of POAG or PACG.…”
Section: Introductionmentioning
confidence: 99%
“…Recent genome wide association studies reveled role of ATP-binding cassette transporter A1, actin filament-associated protein 1, GDP-mannose 4,6 dehydratase, phosphomannomutase 2, transforming growth factor beta receptor III, fibronectin type III domain containing 3B, rho guanine nucleotide exchange factor 12, growth arrest-specific protein 7, forkhead box C1, ataxin-2, thioredoxin reductase 2 with POAG, and PACG showed to be linked to ependymin related 1, choline acetyltransferase, gli-similar protein 3, fermitin family member 2, and dolichyl-phosphate mannosyltransferase subunit 2. [6][7][8][9][10] Furthermore, various candidate gene association studies presented association of single nucleotide polymorphisms with predisposition to development of POAG or PACG. Role of matrix metalloproteinase-9 (MMP-9) variants have been well investigated in different populations as MMP-9 gene is responsible for remodeling of extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%